Delineation and analysis of intra organizational formal and informal relationships through network analysis (Case study: Natural resources organization of Hormozgan province) (مجله جنگل ایران, 2013)
Specialists believe that organizational actors use both formal and informal collaborations to achieve their goals. Although informal relations have been caused restrictions in organization efficiency, but recognition and proper management of these relations could be useful in organizational workflow. Natural Resources Organization of Hormozgan Province, in spite of usual inefficiencies such as lack of sufficient experienced human resources, totally has been successful until now. This research was done in order to delineate and analysis the formal and informal relationship networks between the staffs of this organization and also to answer to these questions: whether informal relations of this organization form a network? Whether this network has positive impacts on formal relations or negative? Is formal relationship network similar to existing organizational chart? In this regard, Network Analysis Approach, UCINET and NetDraw softwares, and input and output degree centralities and betweenness centrality were used. Results showed that informal relations of this organization form a network and its strengths caused to positive impacts on formal relations. Also formal relationship network, more and less, is similar to existing organizational chart. Finally, it is concluded that network analysis as a new approach in managerial problem solving could be so helpful for managers in recognition of effective actors in formal and informal relationship networks and also to increase the human resource efficiency.